Unes lletres de batalla en temps del «Tirant»: Joan Francesc de Pròixita contra don Pero Maça de Liçana - Terol i Roig, Vicent (Caplletra. Revista Internacional de Filologia, 2003)
Publication and study of the “lletres de batalla” (written challenges to combat) exchanged by the Valencian nobles Don Pero Maça de Liçana and Joan Francesc de Pròixita. The affair ended in a combat, with the King of Navarre as judge, which took place at Pau (Bearn) on 5 February 1487. The dispute had a considerable impact on contemporaries and was picked up by historians and later writers.